Determining the Effect of Variation in Colour Gradient Information for Optic Flow Computations - Shobha, B. N.; Kadambi, Govind R.; Shankapal, S. R.; Vershinim, Yuri (New Approaches in Engineering Research Vol. 13, 2021)
Optic flow algorithms provide mapping of 3D velocities on 2D image space. Optic flow is computed on the pair of images which are in sequence and is normally gray scale images. Optic flow computation using Horn and Schunck assumes that brightness consistency is maintained. Colour optic flow has the advantage that optic flow vectors are obtained even when there is a variation of brightness in the input images. The use of colour bands for optic flow is investigated by considering gradients of colour bands and component gradients. Results of applying these two types of gradients to three colour models are presented and analyzed. Decision logic is proposed to select the best colour model for colour optic flow computation based on gradient analysis.